Implementasi Metode Tanya Jawab Dalam Microteaching Untuk Meningkatkan Efektifitas Pembelajaran di Universitas Sunan Giri Surabaya - Idris, Mochammad; El-Yunusi, Muhammad Yusron Maulana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Teachers use learning methods to teach students the subject matter. One of the learning methods is question and answer, which encourages students to participate directly in the learning process and show confidence when giving answers. This study aims to determine the ability of postgraduate students to teach undergraduate students about community empowerment. This study uses qualitative field research methodology as the main instrument to discuss the phenomenon of the research object. This study is very appropriate with qualitative methods because it emphasizes the very natural conditions of the research object and the researcher as the main instrument that determines the research path. The study results indicate the right strategy is needed to improve effective learning. The question-and-answer method used by postgraduate students greatly affects how effectively they learn and the interaction between the two.